Opening Black Boxes is Not Enough – Data-based Surveillance in Discipline and Punish and Today. - Matzner, Tobias (Foucault Studies, 2017)
Discipline and Punish analyzes the role of collecting, managing, and operationalizing data in disciplinary institutions. Foucault's discussion is compared to contemporary forms of surveillance and security practices using algorithmic data processing. The article highlights important similarities and differences regarding the way data processing plays a part in subjectivation. This is also compared to Deleuzian accounts and Foucault's later discussion in Security, Territory, Population. Using these results, the article argues that the prevailing focus on transparency and accountability in the discussion of algorithmic applications needs to be amended with a perspective on different forms of subjectivity and ensuing power relations.